Battery optimizer for android device - Noor Suzieana, Suhaimi (2019)
Smart Battery is a mobile app that will help optimize battery usage. This app is implemented focus for android device users only. The problem faced by some users is they have run out of the phone's battery but no source can recharge the batteries. Not everyone has a power bank and sometimes they may forget to bring it. The solution to solving this problem is by suggesting a mobile app known as Smart Battery (SB) that can help optimize battery usage even minimize it. In the app's main page, it will display health and battery level of health. In this app there are three main functions namely cool battery, charger and mod timer. Smart Battery will smartly handle the android device's internal system for battery details. in Cool Battery page it will display battery temperature. Based on the research done, the best result for charging the battery is between 10c and 30c. Next, the Charger page shows battery status and battery level. For battery status, either in the charging process, does not charge or fully charge. And finally, at the Mode Saver page consists of three subfunction namely Emergency Mode, Long Life Mode and Night Mode. These three modes have same function, where it will turn off Wi-Fi connection, turn off the volume and turn off Bluetooth, but the difference between these three modes is the screen brightness value and the screen timeout value. For Emergency Mode, the screen brightness will be set to 15% and the screen end time is set to 15minute. Even for the Long Live Screen Brightness Screen will be set 30% higher than the Emergency mode and screen timeout is set to 30 minutes. For last mod saver, Night Mode, screen brightness is set 25% and 30 seconds at the end of the screen. Alternatively, the screen brightness will be set to auto when the user pushes the button from the lifesaving mod function. In conclusion, Smart Battery is a simple battery optimizer system that optimizes battery usage can indirectly help users solve their problems